Single-cell-level microfluidics assisted with resuscitation-promoting factor technology (SMART) to isolate novel biphenyl-degrading bacteria from typical soils in eastern China. (15th October 2022) - Jia, Yangyang; Li, Xinyi; Xu, Fengjun; Liu, Zefan; Fu, Yulong; Xu, Xin; Yang, Jiawen; Zhang, Shuai; Shen, Chaofeng
Abstract: Soil microorganisms represent one of the largest biodiversity reservoirs. However, most low-abundance, slow-growing or dormant microorganisms in soils are difficult to capture with traditional enrichment culture methods. These types of microorganisms represent a valuable "microbial seed bank". To better exploit and utilize this "microbial dark matter", we developed a novel strategy that integrates single-cell-level isolation with microfluidics technology and culture with resuscitation-promoting factor (Rpf) to isolate biphenyl-degrading bacteria from four typical soils (paddy soil, red soil, alluvial soil and black soil) in eastern China. Multitudinous bacteria were successfully isolated and cultured; some of the identified clades have not been previously linked to biphenyl biodegradation, such as Actinotalea, Curtobacterium and Rothia . Soil microcosmic experiments validated that some bacteria are responsible for biphenyl degradation in soil. In addition, genomic sequencing and Illumina MiSeq sequencing of 16S rRNA genes indicated that exogenous Rpf mainly promotes the recovery and growth of bacteria containing endogenous Rpf-encoding genes. In summary, this study provides a novel strategy for capturing target functional microorganisms in soils, indicates potential bioresources for the bioremediation of contaminated soils, and enhances our current understanding of the mechanisms involved in the response to exogenous Rpf. Graphical abstract: Image 1 Highlights: A novel strategy was developed to capture target functional microorganisms in soils. Seed banks of biphenyl-degrading bacteria from four soils were established. The mechanism involved in the response to exogenous Rpf was proposed.